If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + -4 = 6w + -6 Reorder the terms: -4 + 4w = 6w + -6 Reorder the terms: -4 + 4w = -6 + 6w Solving -4 + 4w = -6 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. -4 + 4w + -6w = -6 + 6w + -6w Combine like terms: 4w + -6w = -2w -4 + -2w = -6 + 6w + -6w Combine like terms: 6w + -6w = 0 -4 + -2w = -6 + 0 -4 + -2w = -6 Add '4' to each side of the equation. -4 + 4 + -2w = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -2w = -6 + 4 -2w = -6 + 4 Combine like terms: -6 + 4 = -2 -2w = -2 Divide each side by '-2'. w = 1 Simplifying w = 1
| -1x=-4 | | 3y^3-11y^2=3y^2+24y | | 10x-1=(2x+1)(2x+1) | | ln(7x)=2ln(6x) | | 2u-4=-4u+20 | | -18+(-8)= | | .5-3d=2 | | .5d+3=2 | | 7t+4=14t-5 | | 3r=14+10r | | 15n+3-19n= | | (2x-5)(3x-7)= | | 12p+5+3p-5= | | -(3+X)+2-3X=-17 | | x+9=4whatisx | | x+5=-8whatisx | | 1+r^2=1.25 | | x+-9=-3whatisx | | 27=-7x | | 6x-10x+20=0 | | 5(q-7)-3(2q-4)+25=0 | | 6t-5-1+4t=4t | | 2x^3(3x^2-10)=0 | | -3+p=8 | | a^2+2a=99 | | -7x+13=34 | | 9-x=19 | | -5x-9=-29 | | 15ab+20a= | | x*2xy= | | 15x-5=40 | | 8x+5=101 |